FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KESULITAN MAKAN ANAK PRASEKOLAH - Aristiana ' Kesuma; Riri ' Novayelinda; Febriana ' Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this study was to determine the factors which was related to the eating problem in preschool children in PAUD Terpadu Pertiwi Dharma Wanita Persatuan (DWP) Setda Pekanbaru. The design of this study was descriptive correlation with cross sectional approach. This study used stratified random sampling, involving 79 parents of children who attended PAUD Terpadu Pertiwi Dharma Wanita Persatuan  (DWP) Setda Pekanbaru. The data was collected by distributing questionnaires to the parents. The result of this study showed that child involvement (p= 0,021), parental behaviour during meal time (p=0,000),) and meal time control (p=0,036) has correlation with preschool children eating problem while the food presentation(p=0,265) has no correlation with children eating problem. Based of this results, it is recommended to parents, to concern more about children eating problem. Keywords:  Eating problem, preschool children.